Vitamin D Receptor gene polymorphisms taq-1 and cdx-1 in female pattern hair loss - Iman Seleit; Ola Ahmed Bakry; Eman Badr; Mai Mabrouk (Wolters Kluwer Medknow Publications, 2020)
Background: Female pattern hair loss (FPHL) is an important cause of hair loss in adult women and has a major impact on patient's quality of life. It evolves from the progressive miniaturization of follicles that leads to a subsequent decrease of hair density, leading to non-scarring diffuse alopecia, with characteristic clinical, dermoscopic, and histological patterns. Vitamin D receptor (VDR) is expressed in follicular keratinocytes and dermal papilla cells and is shown to have important role in hair growth and regulation of hair cycle. VDR polymorphism was not extensively investigated in hair disorders including FPHL. Aim: To investigate the association between VDR gene polymorphism (Cdx-1 and Taq-1) and FPHL to explore if these polymorphisms affect the disease occurrence or influence its clinical presentation. Methods: A case-control study was conducted on 30 female patients with FPHL and 30 age-matched female healthy subjects, as a control group. Degree of hair loss was assessed by Ludwig grading. VDR gene polymorphisms, Taq-1 and Cdx-1 were investigated by real time polymerase chain reaction. Results: CC genotype, TC genotype, and T allele of Taq-1 were more prevalent in FPHL patients than in control group. They increased disease risk by 12.6, 2.1, and 2.9 folds, respectively. AA genotype, GA genotype, and G allele of Cdx-1 were significantly more prevalent among FPHL patients than in control group. They increased disease risk by 7.5, 5.2, and 5.5 folds, respectively. Conclusion: Taq-1 and Cdx-1 can be considered as risk factors for FPHL. They may play role in disease persistence rather than disease initiation. This association may be explained by failure of new anagen growth and decreased proliferation of hair follicle stem cells. Further studies are recommended to confirm current findings.